Occurrence of Cladocera Populations in Three Treated Sewage Water Fed Ponds in CHRIST (Deemed to be University), Bangalore, Karnataka, India - Karra , Theresa; Sayantan , D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
Cladocerans are a ubiquitously prominent component of zooplankton and limnological systems. In aquatic ecosystems, cladocerans play a significant role in the food chain and secondary production. 620 species of cladocerans have been reported worldwide to far, making them a very old group with Palaeozoic origins. There are currently over 130 species known to exist in India, with Northeastern India having the greatest taxonomic status. A wide variety of small crustaceans known as Cladocera are found in a variety of aquatic settings, from shallow temporary ponds to deep lakes and wide rivers. Cladocerans are a vital source of food for crustaceans, tiny fish, and aquatic insects. Three treated sewage water fed ponds at CHRIST (Deemed to be University), Bengaluru, Karnataka's Main Campus (MCP: 12.555°N, 77.361° E), Bannerghatta Campus (BCP: 12.523°N, 77.354° E), and Kengeri Campus (KCP: 12.514° N, 77.261° E), have been undertaken to study the composition of and occurrence of Cladocera species. In the above study there were 3 species caldoceras observed from all the three study sites of treated sewage water.